Obstructive sleep apnoea triggering autonomic dysreflexia: Isn't it time for sleep studies to be routine in SCI? - Ameerah Alsaqobi (Brain and Spine)
Autonomic dysreflexia is a known complication after spinal cord injury. It is defined as a reflexive increase in blood pressure as a result of a painful or irritating stimulus below the level of the lesion. Although commonly caused by stimuli from the bladder, other rare triggers are still being described. Herein, we present a case with autonomic dysreflexia triggered by obstructive sleep apnoea. A 43-year-old smoker suffered a spinal cord injury after a road traffic accident secondary to multiple cervical spine vertebrae fractures. He presented to our rehabilitation centre 6 months post-injury as a case of complete spinal cord injury with C4 neurological level. Autonomic dysfunction in the form of autonomic dysreflexia was occurring on a daily basis. After exclusion of known inciting factors, it was noticed that early morning episodes of autonomic dysreflexia were persistent. He was also reporting daytime fatigue and sleepiness and multiple night-time awakenings. Therefore, work up for sleep apnoea was done. A diagnosis of moderate obstructive sleep apnoea was made. With continuous positive airway pressure treatment, his daily early morning episodes of autonomic dysreflexia settled. This case illustrates the importance of the pattern of blood pressure elevation to pinpoint specific triggers of autonomic dysreflexia.